Effects of trace elements applied to cows in transition period on serum fatty acid profile - Kizil, M.; Kizil, O. (Hellenic Veterinary Medical Soc, 2022)
The aim of this study was to investigate the effects of trace elements applied to cows during the transition period on serum nonesterified fatty acid profile. The material of this study was consisted of 20 clinically healthy 3-5 year old Simmental cows kept under the same care and feeding conditions. Pregnant cows enrolled in the study were divided into two equal groups with 10 cows in each group. A single dose of 20 ml of thetrace element solution was administered intramuscularly to the cows in the study group three weeks before the parturition. Blood samples were collected for analysis at three different periods: trace element administration time, parturition time and three weeks after parturition. Serum samples were analyzed on the gas chromatography-mass spectrophotometry (GC-MS) device to determine the levels of nonesterified fatty acids. The results showed that; the fatty acid levels determined three weeks before the parturition in the group treated with trace element solution were higher than those detectedat the parturition time and three weeks after parturition. On the other hand, the fatty acid levels determined three weeks before the parturition increased at the time of parturition, and remained at high levelsthree weeks after the parturition in the control group. It was therefore concluded that the trace element supplementation applied to pregnant cows during the transition period prevented excessive increase in serum nonesterified fatty acid levels.
Keywords: Transition period; cows; fatty acid profile; trace element